Redes mercantiles y formación de la familia en el comercio colonial español durante el siglo XVIII - Xabier Lamikiz (Centre de Recherches sur les Mondes Américains, 2008)
This study analyses the close relationship between the creation of trading networks within Spanish colonial trade in the 18th century, and the moment in which the merchants of Cadiz chose to get married and start a family. Following a work of Paloma Fernández Pérez, in which she shows that in the first half of that century Cadiz merchants gave priority to the formation of family networks in order to enter the colonial trade, whereas after the 1750s and 1760s a large proportion of merchants preferred to consolidate their profession first, leaving marriage alliances for later in their lives. The present work explains the reasons for that transformation giving special attention to the changes occurred in the patterns of colonial trade, as a result of the adoption of a system of loose registering of ships in middle of the century. The primary sources used are mainly private letters coming from Spanish America that were intercepted by the British during the 18th century wars.